Vocational High School Revitalization Policy Implementation in Kupang District - DETHAN, Alfan Better Days; PANDIE, David B. W.; DJANI, William (PT Keberlanjutan Strategis Indonesia, 2023)
The majority of SMKs in Kupang district are still not optimal in facing the challenges of revitalization. Vocational schools in Kupang district are still struggling to get out of the Comfort Zone and towards the planned Revitalization. The research method used in this study is a descriptive research method with a qualitative approach. The informants for this research were determined purposively with a total of 50 people and then the researcher would carry out the data collection stages according to Creswell (2016: 254-255) as namely qualitative observation, qualitative interviews, tracking qualitative documents (qualitative documents) and qualitative audio and visual materials. The results of the study found that the implementation of the Vocational High School revitalization policy in Kupang Regency based on the theory of Edward III (1980:21) was found from the side of (1) communication was still not going well. (2) human resources have not run optimally, budget resources are still minimal and equipment resources have begun to appear. (3) the disposition found that the implementor should interpret the importance of this policy as the DNA of SMK as Vocational education. This is reflected in the lack of understanding of the Revitalization of Vocational High Schools in Kupang Regency itself due to the fact that the translation of revitalization is only an option or a choice, not a requirement. (4) the existing bureaucratic structure related to the Vocational School Revitalization Policy in Kupang Regency needs special attention from all lines, both related departments and schools that run it.